PERBEDAAN PERLAKUAN AKUNTANSI ATAS PENGELUARAN PENELITIAN DAN PENGEMBANGAN TERHADAP KINERJA PERUSAHAAN - Riyan Kurniawan; Endang Kiswara (Diponegoro Journal of Accounting, 2012)
Research and development is one of the company operation which has future benefit for company itself. Indeed, the cost for this research and development is in great number. It must be realized that company has to survive in this bussiness activities. Innovation is not only for technology sector, both marketing and production have to be innovated. The data used in this study is a secondary data, namely go public company's annual report in 2007 - 2011, especially listed in the Indonesia Stock Exchange (www.idx.co.id). The sample used a total of 6 companies that reported accounts expense research and development. Data processing method used is analyse descriptive, normality test, homogenity test, and independent sample t test aimed to determine the difference of an accounting method of research and development on the performance of company. Standart that rules this policy is Financial Accounting Standar Board (FASB) No. 19. The results showed that the company which applied capitalization method had higher profitability level than full expensing method. The result of independent sample t test significantly showed difference to Operational Profit Margin and it reversed to Return On Assets and Sales Growth.